Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Prestasi Kerja Pegawai di Kelurahan Bojong Rawalumbu 2024 - Jendro Diu; Tutiek Yoganingsih; Cahyadi Husadha (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to determine and analyze the influence of work motivation and work discipline on employee work performance in Bojong Rawalumbu Subdistrict. This type of research is quantitative. The sample used was 56 respondents from Bojong Rawalumbu Village employees. To test and prove the research hypothesis using the SPSS version 26 application. The results of the research that has been carried out are that the independent variables have a positive and significant effect on the dependent variable. Based on the test results and data analysis for the Work Motivation variable, it was obtained that the t-value was 2.677 > 1.674 (t-table) with a sig of 0.010 < 0.05, meaning that Work Motivation (X1) had a positive and significant effect on Work Performance (Y). Then the Work Discipline variable obtained a t-count value of 5.873 > 1.674 (t-table) with a sig of 0.000 < 0.05, which means that Work Discipline (X2) has a positive and significant effect on Work Performance (Y) and it is known that the f-count is 33.151 > 3.172 (Ftable) with a sig value of 0.000 < 0.05 that simultaneously Work Motivation (X1) and Work Discipline (X2) have a positive and significant effect on Work Performance (Y).